2015
DOI: 10.1080/17457823.2015.1101381
|View full text |Cite
|
Sign up to set email alerts
|

‘The lady is not returning!’: educational precarity and a social haunting in the UK coalfields

Abstract: Drawing on research in de-industrialised coal-mining communities in the north of England, this article focuses on how experiences of some young people might be approached through a notion of precarity linked to the idea of a 'social haunting' of the coalfields. Concentrating on data gathered in the period after the 2010 change of UK government, the article considers how localities suffering under the impact of 'austerity' measures have also witnessed moments of vivid, carnivalesque resurgence linked to celebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…Such a processual understanding of ruin(ation) overcomes the question of how a ruin is defined and by whom. Material remains, of course, can evoke absent pasts, but they are not always fundamental to remembering for those who knew sites before ruination or erasure (Bright, 2016;Byrne & Doyle, 2004). Relatedly, there is also the issue of bodies, life and habitability, bringing into question designations of ruins as abandonment (Dawney, 2020;Safransky, 2014).…”
Section: Theorising and Researching Ruins As Sites Of Traumamentioning
confidence: 99%
“…Such a processual understanding of ruin(ation) overcomes the question of how a ruin is defined and by whom. Material remains, of course, can evoke absent pasts, but they are not always fundamental to remembering for those who knew sites before ruination or erasure (Bright, 2016;Byrne & Doyle, 2004). Relatedly, there is also the issue of bodies, life and habitability, bringing into question designations of ruins as abandonment (Dawney, 2020;Safransky, 2014).…”
Section: Theorising and Researching Ruins As Sites Of Traumamentioning
confidence: 99%
“…Lily I was yanked away from my family and friends My petals were pulled painfully away from me I have now been left in the dark to be stood on repeatedly The poem, written on a sunny Saturday in Rotherham, holds a quality that Gordon (1997) has called "social haunting," which evokes sadness and loss. As in many other post-industrial towns, many inhabitants of Rotherham lost their livelihoods after an extensive period of de-industrialisation begun by the Conservative Prime Minister Margaret Thatcher (Bright, 2016). More recently, a report on a child sexual exploitation case in the town highlighted that ordinary people's issues, -especially girls' and women's -were not being heeded (Jay, 2014).…”
Section: How Do You Speak/make What You Feel?mentioning
confidence: 99%
“…This is compounded by neoliberalized conceptions of aspiration and what constitutes success. Consequently, working‐class youth across genders have been left “adrift from “illegitimate” histories that are their legitimate “heritage” and, at the same time, subject to the traumatic affective legacy of those same histories” (Bright, , p. 316; see also Bright, ). Numerous studies have argued that legacies of industrial worker identities have retained meanings, continuing to form much of the basis of identity formations, gendered projections of societal purpose, and gendered performances (Clarke, ; High, ; MacKenzie et al, ; Walkerdine, ).…”
Section: Deindustrialization: Themes Concerns and Agendasmentioning
confidence: 99%
“…What needs to be appreciated is that "meaning-making in communities such as these [deindustrialized] occurs within a powerful framework of social memory" (Bright, 2011, p. 69) and expectations and valuations of behaviour, appearance, and economic activity are historically conditioned. Bright (2012aBright ( , see also 2012bBright ( , 2011 found that traumatic and difficult histories of deindustrialization have disrupted intergenerational transfers of identity and belonging as older generations struggle to communicate class and place identities in changing circumstances. This is compounded by neoliberalized conceptions of aspiration and what constitutes success.…”
Section: Deindustrialization: Themes Concerns and Agendasmentioning
confidence: 99%